Konstruksi Subjek Feminin dan Posisi Pembaca Paya Nie: Wacana Kritis Sara Mills - Ridwan Ridwan; Nensilianti Nensilianti; Rani Adriani (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2026)
This study examines the construction of women in Ida Fitri’s novel Paya Nie using Sara Mills’ critical discourse analysis, focusing on the subject-object positions of female characters and the author’s strategies for positioning the reader. The method employed was a qualitative description. The results indicate that women are represented as subjects who voice their experiences, yet also face powerlessness and resistance. The character Khadijah is shackled by patriarchy, whereas Ubiet evolves from victimhood into an empowered subject. The author engages the reader through a first-person perspective and conflicts that evoke empathy. It is concluded that women are not merely passive victims but also process agency within the discourse of power and gender.